The Effects of Home Quarantine Duration, Parental Emotional Intelligence, and Family Socioeconomic Status on Children’s Anxiety During the Pandemic: A Survey of 29,550 Parents - Xiang J; Wu J; Lian C; Lin X (Psychology Research and Behavior Management)
Jiaxin Xiang,1,* Jing Wu,2,* Chongyan Lian,3 Xiaoxiao Lin1 1School of Education, Guangzhou University, Guangzhou, Guangdong, 510006, People’s Republic of China; 2Department of Early Childhood Education, Shenzhen Polytechnic University, Shenzhen, Guangdong, 518055, People’s Republic of China; 3Meizhou Technician College, Meizhou, Guangdong, 514071, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Wu, Department of Early Childhood Education, Shenzhen Polytechnic University, Shenzhen, Guangdong, 518055, People’s Republic of China, Email wjirene@szpu.edu.cn Xiaoxiao Lin, School of Education, Guangzhou University, Guangzhou, Guangdong, 510006, People’s Republic of China, Email 1055865964@qq.comBackground: The pandemic has led to unprecedented home quarantine measures affecting children’s anxiety levels due to routine disruptions. This study investigated the role of the length of the quarantine period, parents’ emotional intelligence, and family socioeconomic status (SES) in influencing children’s anxiety.Objective: This study aims to examine the relationship between quarantine duration and children’s anxiety and to explore the mediating role of parents’ emotional intelligence and the moderating role of family socioeconomic status in this relationship.Methods: An online questionnaire surveyed 29,550 parents in Guangdong, Hubei, Henan, and Guangxi provinces of China. The measurement tools used included the Preschool Anxiety Scale, the Family Socioeconomic Status (SES) Scale, and the Emotional Intelligence Questionnaire. The data were analyzed via SPSS 25.0 and Mplus 8.0.Results: A longer quarantine period (as measured by the number of days) significantly reduced children’s anxiety. Parents’ emotional intelligence mediates the relationship between quarantine days and children’s anxiety, explaining 51.79% of the effect. Family SES moderates the mediating effect of parents’ emotional intelligence on children’s anxiety, benefiting higher-SES families more than lower-SES families. Children’s adaptation during the quarantine period demonstrates psychological resilience.Conclusion: The mediating effect of parents’ emotional intelligence accounted for 51.79% of the total effect of quarantine duration on children’s anxiety, with longer quarantine periods associated with decreased anxiety. Family socioeconomic status moderated this effect, benefiting higher-socioeconomic-status families more than lower-socioeconomic-status families. Children’s adaptation during the quarantine period demonstrates psychological resilience. To alleviate anxiety, policies should focus on supporting families with lower socioeconomic status and enhancing parental emotional skills.Keywords: home quarantine, children’s anxiety, emotional intelligence, mental health, pandemic